2019
DOI: 10.1002/aorn.12725
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Risk Factors on Perioperative Pressure Injury Development

Abstract: Patients undergoing operative and other invasive procedures are at high risk for developing pressure injuries. This study aimed to determine the incidence of perioperative pressure injuries in patients who underwent procedures lasting two hours or more in Turkey and the risk factors that affect the development of pressure injuries. Data were collected during the perioperative period. The incidence of perioperative pressure injuries was 40.4%. The results of univariate logistic regression analysis showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
1
21
0
5
Order By: Relevance
“…Several studies have already identified risk factors for IAPI in patients undergoing various types of surgery [ 8 11 ]. Celik et al recruited 151 patients undergoing elective procedures and found that intraoperative vasopressor usage, skin turgor, and diastolic blood pressure ≤60 mmHg were linked with excess risk of pressure injuries [ 8 ]. However, these results were based on univariate analyses, and after adjusting for potential confounders, the authors could not detect any significant risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already identified risk factors for IAPI in patients undergoing various types of surgery [ 8 11 ]. Celik et al recruited 151 patients undergoing elective procedures and found that intraoperative vasopressor usage, skin turgor, and diastolic blood pressure ≤60 mmHg were linked with excess risk of pressure injuries [ 8 ]. However, these results were based on univariate analyses, and after adjusting for potential confounders, the authors could not detect any significant risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Long surgeries are associated with an increased risk of IAPIs because of the increased risk of ischemia and perfusion-reperfusion injury [ 7 ]. Risk factors for IAPIs have already been described in several studies [ 8 11 ], but no research has focused on patients undergoing neurosurgery. These individuals have a high risk of IAPIs because their procedures are longer, continuous irrigation with saline is used during these surgeries, and craniotomy requires use of air and electric drills, which results in vibration.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) 11 da hastaların %37.2'sinde ameliyat sonrası erken dönemde basınç yaralanması oluştuğunu bildirmiştir. Türkiye'de yapılan çalışmalarda oranının %40.4 16 ve %54.8 8 olduğu saptanmıştır. Ameliyat kaynaklı basınç yaralanmalarının cerrahi tedavi geçiren hastaları ciddi oranda etkilediğini gösteren bu bulgular, uluslararası sağlık bakım kalitesinin önemli bir göstergesi olarak kabul edilen 3,9,14,17,18 bu yaralanmaların oluşumunda rol alan risk faktörlerinin belirlenmesinin ve bu faktörlerin kontrolüne yönelik girişimlerin planlanmasının önemine dikkati çekmektedir.…”
Section: Introductionunclassified
“…Ülkemizde ise Çelik ve ark. 2017 yılında, 151 cerrahi hastası ile yaptıkları çalışmada basınç yarası görülme oranını %40.40 olarak saptamışlardır (17). Ameliyathane Kaynaklı Basınç Yaralarında Risk Faktörleri Basınç yaralanmalarını önlemek ve olumsuz etkilerini azaltmak için, basınç yarasına neden olabilecek risk faktörlerinin doğru değerlendirilmesi önemlidir.…”
unclassified